Summary of the recommendations of the EFNS/MDS‐ES review on therapeutic management of Parkinson's disease. Issue 1 (22nd December 2012) - Ferreira, J. J.; Katzenschlager, R.; Bloem, B. R.; Bonuccelli, U.; Burn, D.; Deuschl, G.; Dietrichs, E.; Fabbrini, G.; Friedman, A.; Kanovsky, P.; Kostic, V.; Nieuwboer, A.; et al.
<x xml:space="preserve">Abstract</x> Objective To summarize the 2010 EFNS/MDS‐ES evidence‐based treatment recommendations for the management of Parkinson's disease (PD). This summary includes the treatment recommendations for early and late PD. Methods For the 2010 publication, a literature search was undertaken for articles published up to September 2009. For this summary, an additional literature search was undertaken up to December 2010. Classification of scientific evidence and the rating of recommendations were made according to the EFNS guidance. In cases where there was insufficient scientific evidence, a consensus statement ('good practice point') is made. Results and Conclusions For each clinical indication, a list of therapeutic interventions is provided, including classification of evidence.